Impact of mealtime social experiences on student consumption of meals at school: a qualitative analysis of caregiver perspectives - Leah Elizabeth Chapman; Wendi Gosliner; Deborah A. Olarte; Monica Daniela Zuercher; Lorrene D. Ritchie; Dania Orta-Aleman; Marlene B. Schwartz; Michele Polacsek; Christina E. Hecht; Kenneth Hecht; Anisha I. Patel; Punam Ohri-Vachaspati; et al. (Public Health Nutrition)
Abstract